CLINICAL-EPIDEMIOLOGICAL PROFILE OF PEDIATRIC CASES ATTENDED BY THE MOBILE EMERGENCY CARE SERVICE (SAMU) IN ANÁPOLIS - GOIÁS, FROM JANUARY TO MARCH 2023 (CIPEEX, 2025)
Introduction: The study describes the epidemiological profile of pediatric cases attended by the Mobile Emergency Care Service (SAMU) in Anápolis, Goiás, from January to March 2023. Methodology: This is a descriptive ecological study, using as a source of information the pediatric care records from SAMU in the municipality. Absolute and relative frequencies of the selected variables were calculated. Results: A total of 216 pediatric cases were recorded between January and March 2023. Most patients were male (53.0%) and aged between 1 and 10 years (62.0%). The main location of occurrence was at home (55.5%), predominantly in the afternoon (35.6%), with most incidents occurring on weekends (29.1%). The main reason for care in January was crises—convulsive, asthmatic, anxiety (31.2%), while in February and March, other reasons such as diarrhea, vomiting, malaise, fever, aggression, animal bites, rescues, prostration, injuries, and penetrating events predominated (39.5%; 42.2%). Conclusion: The study highlights the importance of providing specialized care by addressing the main health challenges of the pediatric population (0 to 18 years) in Anápolis.
Keywords: Mobile Emergency Care Services; Clinical-Epidemiological Profile; Pediatric Cases; Anápolis